2016
DOI: 10.21767/2254-9137.100048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Characteristics, Knowledge and Satisfaction with Warfarin Therapy on Willingness to Switch to a New Oral Anticoagulant

Abstract: Background: There are limited studies addressing patient's willingness to switch to a new anticoagulant from warfarin. The goal of this study was to determine the effect of patient knowledge and satisfaction with warfarin therapy on willingness to switch to a new oral anticoagulation therapy in an urban clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Further to this, Ikeda et al [29] found approximately 50% of patients offered to change from warfarin to an NOAC elected not to for reasons including long-term positive experiences with warfarin. Similarly, Wiley et al [30] determined that patients were more willing to switch to an NOAC if satisfaction with warfarin was low. DeCaterina et al [31] found patients switched to NOAC were more often dissatisfied with the OAC treatment, and studies [32,33,34] have also reported between 5 and 13% of patients converting from warfarin to NOAC actually returned to warfarin therapy for reasons including intolerance or bleeds.…”
Section: Discussionmentioning
confidence: 99%
“…Further to this, Ikeda et al [29] found approximately 50% of patients offered to change from warfarin to an NOAC elected not to for reasons including long-term positive experiences with warfarin. Similarly, Wiley et al [30] determined that patients were more willing to switch to an NOAC if satisfaction with warfarin was low. DeCaterina et al [31] found patients switched to NOAC were more often dissatisfied with the OAC treatment, and studies [32,33,34] have also reported between 5 and 13% of patients converting from warfarin to NOAC actually returned to warfarin therapy for reasons including intolerance or bleeds.…”
Section: Discussionmentioning
confidence: 99%